2002
DOI: 10.1007/s10152-001-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and biogeography of shore fishes in the Gulf of Aqaba, Red Sea

Abstract: Shore fish community structure off the Jordanian Red Sea coast was determined on fringing coral reefs and in a seagrass-dominated bay at 6 m and 12 m depths. A total of 198 fish species belonging to 121 genera and 43 families was recorded. Labridae and Pomacentridae dominated the ichthyofauna in terms of species richness and Pomacentridae were most abundant. Neither diversity nor species richness was correlated to depth. The abundance of fishes was higher at the deep reef slope, due to schooling planktivorous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
56
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 72 publications
11
56
2
1
Order By: Relevance
“…Reef fish may thus well be characteristic of-but not restricted to--coral reefs as has already been stated by other authors (Robertson 1998;Bellwood 1998). Species richness correlates negatively with monotony (less diverse substrate) and positively with hole variables (numbers, variation and size), similarly as has been described for rocky shores in higher latitudes (Ferreira et al 2001;Garc铆a-Charton and P茅 rez-Ruzafa 2001) and in the Red Sea (Khalaf and Kochzius 2002). As indicated by our research in BH-GCH, and confirmed by other studies, coral cover alone has little influence on the species richness and abundance of fish (Roberts and Ormond 1987;Luckhurst and Luckhurst 1978), and coral reef community structure (in general and fish community in particular) seems to be a complex, indirect and non-linear consequence of reef structure and environmental conditions (Bradbury and Young 1981).…”
Section: Distribution Patterns As Related To Water Depthsupporting
confidence: 69%
“…Reef fish may thus well be characteristic of-but not restricted to--coral reefs as has already been stated by other authors (Robertson 1998;Bellwood 1998). Species richness correlates negatively with monotony (less diverse substrate) and positively with hole variables (numbers, variation and size), similarly as has been described for rocky shores in higher latitudes (Ferreira et al 2001;Garc铆a-Charton and P茅 rez-Ruzafa 2001) and in the Red Sea (Khalaf and Kochzius 2002). As indicated by our research in BH-GCH, and confirmed by other studies, coral cover alone has little influence on the species richness and abundance of fish (Roberts and Ormond 1987;Luckhurst and Luckhurst 1978), and coral reef community structure (in general and fish community in particular) seems to be a complex, indirect and non-linear consequence of reef structure and environmental conditions (Bradbury and Young 1981).…”
Section: Distribution Patterns As Related To Water Depthsupporting
confidence: 69%
“…Comparison of differences in fish species richness and abundance on reefs and seagrass plots with urchins (+) compared to those without urchins (-). A 2-way ANOVA indicated that presence of urchins strongly affected fish abundance (p < 0.001) and observed species richness (p < 0.004), while habitat had highly significant effect on fish abundance (p < 0.01) and observed species richness (p < 0.001) documented in the Red Sea (Khalaf & Kochzius 2002). The presence of seagrass in a quadrat might have a similar effect, because the seagrass leaves offer a stable surface for periphyton growth, as well as limited refuge from predators.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, a systematic approach that simultaneously examines as many complexity variables as possible to determine which are the most important factors is needed. For this study, 5 main habitat-complexity variables recurring in the literature were identified: (1) topographic complexity or rugosity of the substrate (Risk 1972, Luckhurst & Luckhurst 1978, Roberts & Ormond 1987, Jennings et al 1996, Chabanet et al 1997, Ohman & Rajasuriya 1998, (2) substratum diversity (Roberts & Ormond 1987, Ohman & Rajasuriya 1998, (3) variety of refuge hole sizes (Roberts & Ormond 1987), (4) vertical relief or height of substrate architecture (Luckhurst & Luckhurst 1978, Molles 1978) and (5) percentage hard substrate (Cohen et al 1993, Guidetti 2000, Khalaf & Kochzius 2002. The effects of each of these variables on the local fish assemblage were tested in a field experiment, and this study is one of the first experimental attempts to simultaneously compare the effects of all these habitat complexity variables.…”
Section: Introductionmentioning
confidence: 99%
“…This species is reported only at the northern site and not present elsewhere along the Jordanian coast [12]. The coral reef fishes along the Jordanian coast are dominated by Pomacentridae, followed by Anthininae (subfamily of Serranidae) and Labridae [28]. Visual censuses of fish assemblages in this study revealed the dominance of Lethrinidae, followed by Pomacentridae, Serranidae, Siganidae and Labridae.…”
Section: Open Accessmentioning
confidence: 48%